“Thaifying” Kodály: Developing an Applied Prototype Pedagogical Method for 7th-Grade Students in Thailand - Jumneanpan, Wipawan; Pidokrajt, Narongchai (Malaysian Journal of Music, 2025)
This study focused on creating an applied prototype of a Kodály-based pedagogical method for 7th-grade students in the Thai education system and on evaluating its implementation in a school in Central Thailand. The research objectives were: 1) to develop Kodály-based lessons to improve students’ musicianship skills; 2) to analyse the learning process of students taught with this approach; 3) to gather students’ views on the method; and 4) to obtain feedback from music educators, academics, and experts on its applicability. The sample comprised 18 students and 15 respondents from the music education community. The findings showed clear improvement in musicianship skills, and students reported increased confidence and engagement, suggesting that Kodály-based instruction can help make complex concepts more accessible. Feedback from the specialist group affirmed the method’s suitability for strengthening foundational skills and its adaptability within Thai educational settings. The applied prototype incorporates culturally grounded components, including a locally composed Thai song and the use of Thai alphabet characters (ด–ร–ม–ซ–ล) in modified stick notation, together with a locally adapted quarter rest (yood). The study demonstrates how Kodály’s pedagogical principles may be reinterpreted through context-specific modifications and provides a model for culturally responsive music education.